SAT0497 Follow-up of disease activity in hungarian patients with idiopathic inflammatory myopathy. (12th June 2018) - Bodoki, L.; Nagy-Vincze, M.; Griger, Z.; Szekanecz, Z.; Dankó, K.
Abstract : Background: Assessing disease activity in patients with myositis is an important goal. A method called Disease Activity Core Set Measures was established by International Myositis Assessment and Clinical Studies Group (IMACS) for evaluating activity of myositis. This assesses the manifestations of myositis which are thought to be reversible that result directly from the inflammatory process. Objectives: In this prospective study authors aimed to monitoring disease activity in Hungarian myositis patients treated at the Autoimmune Outpatient Clinic, Department of Clinical Immunology, University of Debrecen. First, disease activity data of poly (PM) – and dermatomyositis (DM) patients were compared. Secondly, by patients with active disease, the correlations between the components of Disease Activity Core Set Measures were studied. Methods: During the three-year follow-up period, at every single visit, authors evaluated disease activity using factors of Disease Activity Core Set Measures and patients filled Health Assessment Questionnaire (HAQ). Only those patients who appeared at least three times during the follow-up period were selected. Statistical analysis was made using SPSS 17.0 statistical software. Results: Collection of data from 219 patients (age: 44.93 years, female: male ratio 2.98:1) happened in a total of 1101 outpatient visits. The 107 PM patients had statistically significant higher physician and patient visual analogue (VAS) and myositis disease activity assessment tools scores than the 61 DM patients, with the exception of cardiovascular disease activity. Activity of skin lesions was significant higher in DM patients. By the 44 patients, who had an active disease, the MMT scores gave significant negative correlations with HAQ scores (R=−0.536 and p<0.001) and CK levels (R=−0.387 and p<0.001). The physician and patient VAS gave strong negative correlations with MMT scores (R=−0.714 and p<0.001 and R=−0.730 and p<0.001, respectively) and positive correlations with HAQ scores and CK levels (physician VAS vs. HAQ R=0.691 and p<0.001; patient VAS vs. HAQ R=0.629 and p<0.001; physician VAS vs. CK R=0.622 and p<0.001; patient VAS vs. CK R=0.615 and p<0.001). Conclusions: As far as we know, this is the first study which compares the activities of PM and DM patients based on the IMACS system. According to our data, we can conclude that PM patients had more severe muscle symptoms and extramuscular manifestations. Secondly, as seen in other previous studies, calculations in patients with active myositis showed a clear correlation between the most important components of Disease Activity Core Set Measures. Disclosure of Interest: None declared